FAKTOR-FAKTOR YANG MEMPENGARUHI SKEPTISISME PROFESIONAL AUDITOR DALAM PENUGASAN AUDIT - Rosa De Lima Chendy Alfa; Stefani Lily Indarto (Jurnal Akuntansi Bisnis, 2013)
The auditor is required to have a skeptical attitude on the evidence given by his clients in order to produce a good quality audit. Auditor's professional skepticism is an attitude that is always questioning and critical evaluation of the audit evidence. Professional skepticism, the auditor is required to minimize the mistakes made during the investigation auditors on the financial statements. Public confidence in the quality of public accounting firm will be higher if the profession is to apply high quality standards for the implementation of the professional work done by members of the profession, so that auditors can be expected to exhibit professional skepticism attitude. However, on the one hand people are still often dubious level of professional skepticism by auditors owned KAP. This study aimed to examine the effect of trust, fraud risk assessment, internal locus of control, professional ethics, competence, and risk audits of professional skepticism. Respondents in this study is an auditor in public accountant in Yogyakarta. The results of this study the lower confidence auditor, the higher the professional skepticism by auditors indicated. conversely, higher level of fraud risk assessment, internal locus of control, professional ethics, competence, and audit risk held by the auditor, the higher the professional skepticism by auditors indicated